Exposure to vinyl chloride and angiosarcoma of the liver: a report of the register of cases. Issue 11 (November 1985) - Forman, D; Bennett, B; Stafford, J; Doll, R
Abstract : The Association of Plastic Manufacturers in Europe maintains a register of all cases of angiosarcoma of the liver (ASL) resulting from exposure to vinyl chloride monomer (VCM). This register has recorded all known VCM related cases of the disease worldwide that have been histologically confirmed. Although likely to be incomplete, it is the most comprehensive tabulation of such cases available and, by the end of 1984, 118 men had been registered. The information from analysis of the cases currently on the register is used to make an approximate projection of the number of cases to be expected in the future. The conclusion from this projection is that the industry is reaching the halfway stage in the appearance of VCM related ASL.